Dielectric Behavior of Low Microwave Loss Unit Cell for All Dielectric Metamaterial - Tianhuan Luo; Bo Li; Qian Zhao; Ji Zhou (International Journal of Antennas and Propagation)
With a deep study of the metamaterial, its unit cells have been widely extended from metals to dielectrics. The dielectric based unit cells attract much attention because of the advantage of easy preparation, tunability, and higher frequency response, and so forth. Using the conventional solid state method, we prepared a kind of incipient ferroelectrics (calcium titanate, CaTiO3) with higher microwave permittivity and lower loss, which can be successfully used to construct metamaterials. The temperature and frequency dependence of dielectric constant are also measured under different sintering temperatures. The dielectric spectra showed a slight permittivity decrease with the increase of temperature and exhibited a loss of 0.0005, combined with a higher microwave dielectric constant of ~167 and quality factor Q of 2049. Therefore, CaTiO3 is a kind of versatile and potential metamaterial unit cell. The permittivity of CaTiO3 at higher microwave frequency was also examined in the rectangular waveguide and we got the permittivity of 165, creating a new method to test permittivity at higher microwave frequency.